Atorvastatin disrupts primary human brain microvascular endothelial cell functions via prenylation‐dependent mitochondrial inhibition and oxidative stress. (27th October 2020) - Tan, Qian; Yu, Danfang; Song, Lin
Abstract: Primary human brain microvascular endothelial cell (HBMEC) is the major component of the blood–brain barrier (BBB). Atorvastatin, a HMG‐CoA reductase inhibitor, is a cholesterol‐lowering drug commonly used to reduce the risk for cardiovascular disease. Numerous studies have reported the pleiotropic effects of atorvastatin on endothelial cells, but the findings are controversial and inconclusive. In addition, little is known about the biological effects of atorvastatin on HBMEC. In this work, we demonstrate that atorvastatin at micromolar but not nanomolar concentrations induces dysfunctions of a number of HBMEC events, including differentiation into capillary network, migration and growth but not cell adhesion. We further show that the inhibitory effects of atorvastatin on HBMEC are independent of angiogenesis stimulators. Atorvastatin induces HBMEC apoptosis even in the presence of vascular endothelial growth factor (VEGF) and serum. Mechanism studies indicate that atorvastatin at micromolar concentration leads to protein prenylation inhibition, mitochondrial dysfunction and thereby subsequent oxidative stress and damage in HBMEC. Rescue experiments confirm that atorvastatin inhibits HBMEC functions via prenylation‐dependent mitochondrial inhibition. Our work reveals the inhibitory effects of atorvastatin on HBMEC and suggests the possible negative influence of atorvastatin in blood–brain barrier.